2002
DOI: 10.1056/nejmoa020265
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trends in the Incidence of and Survival with Heart Failure

Abstract: Over the past 50 years, the incidence of heart failure has declined among women but not among men, whereas survival after the onset of heart failure has improved in both sexes. Factors contributing to these trends need further clarification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
1,209
12
90

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,923 publications
(1,352 citation statements)
references
References 34 publications
41
1,209
12
90
Order By: Relevance
“…Previous national studies revealed a decline in all‐cause mortality,12, 22 and a similar pattern was noted internationally 10. However, there was no statistically significant change in trend in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Previous national studies revealed a decline in all‐cause mortality,12, 22 and a similar pattern was noted internationally 10. However, there was no statistically significant change in trend in our study.…”
Section: Discussionsupporting
confidence: 86%
“…There was a striking increase in its prevalence from the 1970s through the 1990s, during which time it reached an epidemic level 3, 4. Although recent reports suggest that the incidence of HF has plateaued in the general population and is decreasing in some groups,1, 5, 6 an estimated 915 000 individuals are still diagnosed as having HF in the United States each year. Furthermore, because of the aging of the population and improved survival after diagnosis, the prevalence of HF is still increasing and is estimated to increase by 46% from 2012 to 2030, which will result in >8 million adults with a diagnosis of HF 2, 7…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that extracardiac treatment is also responsible for comparable proportions of mortality because of HF at the end of 3 years also (60 and 62% in the IAHF and NIAHF, respectively). These mortality rates are all substantially higher, within all age groups within this cohort, than those reported in the most recent epidemiological studies for HF in the general population where, although survival has improved, the absolute mortality rates for HF remain approximately 50% within 5 years of diagnosis 13, 14. In the ARIC study, the 30‐day, 1‐year, and 5‐year case fatality rates after hospitalization for HF were 10.4, 22, and 42.3%, respectively 15…”
Section: Discussionmentioning
confidence: 61%